Can an obligation bridge Germany's PV capacity gap? Insights from a regional case study - Felix Meurer; Marco Sebastian Breder; Michael Bucksteeg; Hannes Hobbie; Dominik Möst; Hendrik Scharf; Christoph Weber (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2024)
Reaching Germany's PV expansion goal requires regulatory instruments that promote new investments in PV rooftop installations complementing other environmental measures and enhancing coordination among stakeholders and alongside the building lifecycle. In great regional detail, this paper examines how an obligation tied to new building construction and renovation in the residential and non-residential sectors might further PV expansion and considers its socio-economic implications. The findings suggest that while a PV obligation could significantly advance national energy goals, it would contribute only a fraction of the annual growth in PV capacity needed. The research identifies a positive correlation between the impact of PV obligations for non-residential building construction and regional gross domestic product, indicating a potential distributive effect where less affluent regions lag further behind in sustainable energy production. In conclusion, a PV obligation could play a key role in future German energy legislation, but broader measures must complement it. Policymakers need to carefully balance the PV obligation's potential for capacity growth with the risk of undermining public acceptance of the energy transition.
Keywords: 330; Obligation; Building; Renovation; Residential; Non-Residential